DIFFERENCE IN SURFACE FITTING WITH STANDARD AND MATRIX TOPOLOGY: Received: 18th July 2023 Revised: 01st November 2023, 16th November 2023, 24th November 2023 Accepted: 31st July 2023 - Milan Ćurković,; Andrijana Ćurković,; Damir Vučina, (MATTER: International Journal of Science and Technology, 2024)
This paper presents the impact of the surface topology of the scanned 3D object on parametric fitting. Whether it is a simple NURBS (Non-uniform rational B-spline) or a more complex hierarchical spline version, it is important to apply the fitting procedure. Here we describe the differences between fitting a surface with a given topology as a result of a 3D scanning system and a matrix topology of the surface, where the original surface is replaced by the result of a preset number of sections of the original geometry. We use the matrix and the free-form distribution. The former is more stable with respect to the distribution of the control point, the latter is numerically more suitable. In the future, we plan to adopt the free-form distribution to utilize the advantages of both distributions.